Meiotically Stable Natural Epialleles of Sadhu, a Novel Arabidopsis Retroposon - Rangwala, Sanjida H; Elumalai, Rangasamy; Vanier, Cheryl; Ozkan, Hakan; Galbraith, David W; Richards, Eric J (PLoS genetics, 2006)
Epigenetic variation is a potential source of genomic and phenotypic variation among different individuals in a population, and among different varieties within a species. We used a two-tiered approach to identify naturally occurring epigenetic alleles in the flowering plant Arabidopsis: a primary screen for transcript level polymorphisms among three strains (Col, Cvi, Ler), followed by a secondary screen for epigenetic alleles. Here, we describe the identification of stable, meiotically transmissible epigenetic alleles that correspond to one member of a previously uncharacterized non-LTR retroposon family, which we have designated Sadhu. The pericentromeric At2g10410 element is highly expressed in strain Col, but silenced in Ler and 18 other strains surveyed. Transcription of this locus is inversely correlated with cytosine methylation and both the expression and DNA methylation states map in a Mendelian manner to stable cis-acting variation. The silent Ler allele can be converted by the epigenetic modifier mutation ddm1 to a meiotically stable expressing allele with an identical primary nucleotide sequence, demonstrating that the variation responsible for transcript level polymorphism among Arabidopsis strains is epigenetic. We extended our characterization of the Sadhu family members and show that different elements are subject to both genetic and epigenetic variation in natural populations. These findings support the view that an important component of natural variation in retroelements is epigenetic.